i-Guess enterprise / Abdul Shafiq Abdul Razak...[et al.] - Abdul Razak, Abdul Shafiq; Samsuddin, Syahirah; Mohd Kasri, Nur Atiyah; Sulaiman, Aqilah Husna; Mohammad Hatta, Siti Nadhirah (2016)
Entrepreneurship is a process innovation and new venture creation through four dimensions which includes individuals, organization, environment and institution. Entrepreneurs are individual who actively form are lead their own business nurture them for a growth and prosperity. In order to form a business, there are quiet numbers of phase that should be understood and develops by entrepreneur. i-Guess Enterprise is a partnership company ventured by five partners such as General Manager, Administration Manager, Operational Manager, Financial Manager, and Marketing Manager. Each partner will hold different position in managing the business. i-Guess is a product business that offers a new product that can indicate the level of the cooking gas and detect if there is a leakage in that gas. To make it more attractive and interesting, this company decided to make some innovation by implying creativity and modern element in this cooking gas. Nowadays, safety is one of the important things in any products making so a new safety equipment might be a new attraction to people. This company try to implement the attitude of the Malaysian people which is careless about the safety of their lifestyle to the product. This is because most of the Malaysian people is busy and doesn't have enough time to check where the cooking gas has a leakage or not. Besides that, we have done some research that Malaysia is one of developed country and it quite busy during day time. Normally people who work during office hour and students do not have much time. So, with our new innovation, they can just get the gas dedicator to ease their life because they can know when the cooking gas is almost empty and also can make some preparation if the cooking gas is leakage and safe their life. It is easy and simple as that. i-Guess Enterprise have a long term target of expanding business as to have many branches throughout Malaysia. Besides that, all manager are determined to make a strong impact in this industry and hope to slowly regain the trusts of the customers so that this company will be able to dominate the market and establish this company brand to be as strong as possible. This company are promoting gas dedicator for the first month to attract customers to buy this products with an affordable price.